2019
DOI: 10.1002/anzf.1394
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Validity of Bowen Theory in Southern European Countries

Abstract: We present a comparison between Italy, Spain, Greece, and Portugal to test the cross‐cultural validity of the Differentiation of Self Inventory Revised (DSI‐R) Scales of emotional cut‐off (EC) and emotional reactivity (ER). Our study focuses on the importance of in‐depth analyses of the differentiation of self‐constructs from a cross‐cultural perspective and reflects on the possibility of conceptualising the universality of Bowen theory in southern European countries. The study involved 1,807 healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…For instance, Bowen posited that high levels of differentiation would be associated with better mental health outcomes. The same has been corroborated by many studies in the West (Jankowsky et al, 2013; Lampis et al, 2019;Skowron, 2000). Data also favours the association that exists between low levels of differentiation and psychological distress (Murdock & Gore, 2014;Tuason & Friedlander, 2000).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…For instance, Bowen posited that high levels of differentiation would be associated with better mental health outcomes. The same has been corroborated by many studies in the West (Jankowsky et al, 2013; Lampis et al, 2019;Skowron, 2000). Data also favours the association that exists between low levels of differentiation and psychological distress (Murdock & Gore, 2014;Tuason & Friedlander, 2000).…”
Section: Introductionsupporting
confidence: 52%
“…These studies have indicated that the terms used are differently understood and interpreted by people from non-Western cultures. The Fusion with Others (FO) subscale has been particularly vulnerable to varying interpretations due to the differing nature of family relationships in various cultures (Chung & Gale, 2006;Kim et al, 2015;Lampis et al, 2019;Lam & Chan-So, 2013). In 2015, Rodriguez-Gonzalez and others conducted a study of Spanish adult participants after translating and back-translating the DSI-R and found that only two of the four subscales (Emotional Reactivity and Emotional Cutoff) were valid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be productive when alone or in relationships (Papero, 2015). Lampis et al (2019) investigated the structures of differentiation of the intercultural self in their study. They stated that more studies are needed between different cultural groups in order to have more detailed information about the concept of differentiation of self.…”
Section: Differentiation Of Selfmentioning
confidence: 99%
“…Why Bowlby, Kohut, and Bowen? The most obvious way to answer this question is by pointing to the enormous influence that each of these scholars has had on the theories and practices informing family therapy and other fields in the counselling, therapy, and psychology professions. Moreover, their models of the way in which selves are formed and transformed in relational systems are among the most empirically studied and validated theories in psychology (e.g., Banai, Mikulincer, & Shaver, 2005;Brown, 2020;Jankowski & Hooper, 2012;Kerr, 2019;Lampis et al, 2019;Roisman et al, 2007). But this does not yet answer the more specific question: Why try to link these three influential and well-validated theories?…”
mentioning
confidence: 99%